The Cost of Air Pollution in the City of Yazd - Rahman Khoshakhlagh; Marzieh Sotodehnia Corani (Pizhūhishnāmah-i Iqtiṣād-i Inirzhī-i Īrān, 2012)
The purpose of this research work is the evaluation of the significant factors explaining concentration of air pollution in the city of Yazd and then explaining how the expected damage to the pollution can be evaluated. After estimating the costs due to air pollution created environmental net domestic (EDP) production is damaged. EDP obtained is 4887930630 and this amout is based upon our research that shows each resident is willing to pay 4937 Rials where is what is being cost of the present is 1627.